Common regulation of administrative inspection in Peruvian law - Morón Urbina, Juan Carlos (2020)
By the way of the inclusion of inspection activity in the Peruvian General Administrative Procedure Law, the author examines the most important characteristics of this institution, such as its juridical characterization, the powers of the administration regarding this activity, the duties of the Administration with the inspected, the rights and duties of the governed that are inspected, and also the different ways of conclusion of inspection.